Embracing faith and desire
1 online resource (232 pages).
Keywords: Embracing Faith and Desire investigates the intersection of gender, sexuality, and religion from an anthropological lens. Taking women's, non-binary, and queer religious life-worlds in Muslim and Christian contexts as a cross-cutting research theme, the book brings together scholars from different disciplines and regional contexts who are interested in the interconnectedness of gender dynamics, queerness, and religious principles.The explosive growth of contesting religions, especially in a Christian-Muslim context, represents a distinctively religious-political dynamic within globalization. It disrupts the global world order, influences hegemonic negotiations within and across nation-states, and shapes self-imaginations and practices of social actors. Consequently, it carries far-reaching political, religious, economic, and social ramifications. Embracing Faith and Desire explores these ramifications on various levels. The volume thereby contributes to debates on intersectionality, queer, and religious approaches alike by showcasing how the scopes and scales of action and the constructive shaping of self-images, social relations, and political actions of people are fundamentally dependent upon religious, gendered, and sexualized backgrounds. Embedding the contributions in the anthropology of religion, anthropology of gender, and queer anthropology, the book reconfigures our understanding of lived religion through the lens of gendered and queered imaginations, practices, and ideologies.